Lithostratigraphy and Limestone Microfacies of the Jafnayn Formation (Paleocene to Early Eocene, Al-Khod, Sultanate of Oman): Deposition in a Restricted Lagoon with Intervals of Open Marine Conditions - Frank Mattern; Andreas Scharf; Abdul Razak Al-Sayigh; Abdulaziz Al-Mamari; Laura Galluccio; Sundus Al-Ghaiti; Gianluca Frijia; Lorenzo Consorti; Maram Al-Saadi; Fatema Al-Jabri (Geosciences)
We studied the Jafnayn Formation’s lithostratigraphy, microfacies, depositional environment, and uncertain presence of the Paleocene/Eocene boundary and present the first detailed analysis of a 127-m-thick section using the standard microfacies (SMF)/facies zone (FZ) system. The formation is dominated by foraminiferal grainstones and packstones of SMF 18-FOR, followed by peloidal grainstones and packstones of SMF 16. Coral-red algae floatstones of SMF 8 occur sporadically. SMF 18-DASY appears only once. SMF 16 and 18-FOR suggest a restricted lagoon, whereas SMF 8 and 18-DASY reflect episodic open marine lagoonal conditions. The section consists of four lithostratigraphic units. Considerable detrital quartz near the base (Unit 1: 22%; sand, sandstone, conglomerate) and top (Unit 4: 40%; sand) coincides with a restricted lagoon affected by near-shore processes (base) and near-shore conditions (top). Open marine conditions show an elevated bioclast diversity in units 3 and 4. Unit 2 displays very thickly-bedded limestones of the restricted lagoon. The lagoon barriers likely consist of foraminifera and other allochems that were reworked from the lagoon to form shoals. Coral remains in units 3 and 4 suggest that coral build-ups in the upper part of the formation protected the lagoon as well. The early Eocene age of several basal Alveolina species in the lowermost 9 m of the studied section indicates that the section is incomplete, with the late Paleocene part and meters-thick basal yellow marl missing. The Paleocene/Eocene boundary is unexposed.